Into the uncanny valley: Simulation versus simulacrum?. Issue 10 (5th June 2020) - Johnston, Jennifer Laura; Kearney, Grainne P; Gormley, Gerard J; Reid, Helen
Abstract : Adding to the Cross‐cutting edge series, Johnston et al. introduce readers to the postmodern concept of the simulacrum and explore its relevance to the growing field of simulation education.